How Information-Seeking Behavior, Essential Technologies, and Resilience Enhance the Academic Performance of Students - Miraj, Muhammad; Chuntian, Lu; Mohd Said, Ridzwana; Osei-Bonsu, Robert; Rehman, Ramiz ur (Frontiers in Psychology, 2021)
The current study explores how students’ scholarly accomplishments might increment due to specific fundamental causes. The student’s academic performance was prioritized as a dependent variable, and the independent indicators chosen were “information seeking, IT ability, reading/writing capacity, and resilience.” At the same time, age, gender, marital status, and family income were included in the control variables. The research subject samples were limited to (N= 288) master’s students from three mega-universities in Islamabad, Pakistan. Forward regression analysis was performed in the current research to decide the impact of the indicators. The results indicate that information seeking affects academic performance positively and significantly. Essentially, the study revealed that IT skills make a fundamentally positive and significant impact on academic performance. Reading and writing influenced academic performance considerably. In addition, resilience affected academic performance emphatically and essentially. Further, this research also noted the relationships between (information-seeking behaviors, IT ability, reading/writing capacities, and resilience capabilities) and students’ academic performance. These variables have a positive impact on students’ academic performance.